Human and World: Fichte and Wang Yangming on the Highest Good - Jun Wang (Religions)
In comparative philosophy, the study of Fichte and Wang Yangming has been largely overlooked. This article compares their views on the highest good and their approaches to the human–world relationship. Fichte sees the highest good as the realization of practical reason, achievable through religious faith and love for God, enabling individuals to transcend sensual desires and unify with God. Religious faith connects individuals to a higher existence, fostering moral actions. Wang Yangming, however, defines the highest good as the manifestation of conscience within, emphasizing internal cultivation and moral practice to achieve the unity of knowledge and action. Fichte’s approach relies on religious faith, while Wang Yangming’s focuses on self-cultivation. This study reveals the complementarity between Chinese and Western perspectives on the highest good, offering a new lens for cross-cultural dialogue and insights into the complex relationship between humans and the world.